Digital finance and migrant workers' urban integration: The mediation effect of the gender-earning gap - Yang, Zhiheng; Liu, Tiantian; Xiao, Yao (Frontiers in Public Health, 2022)
Introduction In the context of the wide application of digital finance, whether digital finance promotes or inhibits migrant workers' urban integration is an important issue. Methods Based on microdata from the Chinese Social Survey (CSS) in 2019, we examined the mediation effects of inclusive digital finance on migrant workers' urban integration. Results The empirical results showed that digital finance promotes migrant workers' integration into urban life and has positive effects. When the digital finance index increases by 1 unit, the urban integration of migrant workers also increases by 0.599 units. The usage depth and digitization degree of digital finance are positively correlated with the assimilation process of urban migrant workers, with coefficients of 0.690 and 1.282, respectively. Using the intermediary effect model, it was found that the development of digital finance promotes migrant workers' integration into urban society by narrowing the gender gap in income. One unit of digital finance increases the income of female migrant workers by 144.4% points greater than that of male migrant workers. It significantly improves the ability of female migrant workers to obtain wealth and promotes their integration into cities and family migration. Discussion It is necessary to strengthen the promotion and utilization of digital finance to enhance its positive impact on the assimilation process of urban migrant workers by strengthening the construction of digital financial infrastructure, improving supporting policies related to the development of digital finance and improving the financial literacy of migrant workers, especially female migrant workers.